2012
DOI: 10.1159/000343756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Electrical Stimulation and Posterior Tibial Nerve Stimulation in the Treatment of Overactive Bladder Syndrome

Abstract: Aim: To compare the effects of transvaginal electrical stimulation (ES) and posterior tibial nerve stimulation (PTNS) in the treatment of overactive bladder syndrome (OAB). Methods: Women applying with symptoms of urgency, frequency, and nocturia with or without incontinence and diagnosed with OAB were divided into an ES or PTNS group. Bladder diary, urodynamics, 1-hour pad test, and King’s Health Questionnaire were performed before and after treatment. ES was applied for 20 min, 6–8 weeks with pulses of 10–50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…It is thought that pelvic floor muscle stimulation leads to reflex contraction of the striated paraurethral and periurethral muscles with simultaneous reflex inhibition of the detrusor muscle. Ugurlucan et al (2013) [17] compared the effects of transvaginal electrical stimulation (ES) and PTNS in a randomized controlled trial. The study demonstrated that there was no statistically significant difference between the two groups in objective measurements.…”
Section: Ptns Compared With Transvaginal Stimulations and Pelvic Floomentioning
confidence: 99%
“…It is thought that pelvic floor muscle stimulation leads to reflex contraction of the striated paraurethral and periurethral muscles with simultaneous reflex inhibition of the detrusor muscle. Ugurlucan et al (2013) [17] compared the effects of transvaginal electrical stimulation (ES) and PTNS in a randomized controlled trial. The study demonstrated that there was no statistically significant difference between the two groups in objective measurements.…”
Section: Ptns Compared With Transvaginal Stimulations and Pelvic Floomentioning
confidence: 99%
“…The result showed that both ES and PTNS were effective in OAB treatment with significant improvement in subjective and objective parameters, but without significant difference between the two groups. 20 Thus, PTNS is considered more effective than TENS and suggested as a cheaper, safer and less invasive alternative to SNS and ES. 21 …”
Section: Electrical Stimulationmentioning
confidence: 99%
“…32,71 -75 In another study comparing the effects of ES and PTNS in the treatment of OAB, both treatments were effective, but the number of patients who describe themselves as cured in the ES group was significantly higher than PTNS. 76…”
Section: Efficacies Of Pelvic Floor Es For Oab (Including Uui) And/ormentioning
confidence: 99%